Buffalo milk quality in southern Italy: trace elements & endocrine disruptors. A One Health analysis - Luigi Jacopo D’Auria (Revista Científica)
The production of buffalo milk and its derivatives represents an important economic sector in Southern Italy, especially in the Campania region. Buffalo milk is mainly used for the production of “mozzarella di bufala”, a soft, un-ripened cheese variety of the pasta filata family, highly appreciated worldwide for its good characteristics and particular taste. In the period 2015-2018, buffalo milk production in Italy increased by 27%, from 195,270 to 247,158 tons. The entire buffalo milk production chain can be contaminated with trace elements (TE), bisphenol (BPA) and others endocrine disruptors (EDs). The source of these pollutants can come from feed, forage and food additives. Given the importance of this foodstuff in the Campania region, the presence of BPA and EDs was investigated in all production stages of the buffalo supply chain, from water to feed to milk. The aim of this study was also to evaluate how the geochemical impact of agricultural soils can influence the chemical element profile of buffalo milk. Using a “One Health” approach, the fate of trace elements and endocrine disruptors was considered, starting with the transfer of these elements to buffalo milk after feed ingestion by the animal. Trace element analysis came from different areas of the Campania Region, where buffalo farms were randomly selected for sampling of milk (n:69). At the same way, samples of milk (n:46) and serum (n:190) were collected from 10 buffalo farms in the Campania Region for analysis of endocrine disruptors. For both research lines, forage, feed (n:207) and groundwater (n: 486) samples were also collected. The results of samples collected from buffalo farms distributed throughout the Campania region were statistically analysed using Cluster Analysis (CA) and Factor Analysis (FA). The results indicate that among the endocrine disruptors investigated, BPA is present in all farms studied. Bisphenol contamination has been found in all types of feed and its presence in buffalo milk can be mainly attributed to feed, especially feed additives. In buffalo milk, BPA is present at levels between 0.5 and 5.6 ng/mL. Regarding the presence of metals, of the twenty trace elements analysed, only lead is regulated in the EU and no sample exceeded the maximum limit (LM = 0.02 mg/kg). Potentially toxic elements such as chromium (< 0.141 mg/kg), cobalt (< 0.008 mg/kg), manganese (< 0.035 mg/kg), selenium (< 0.044 mg/kg), vanadium (< 0.016 mg/kg), zinc (<4.31 mg/kg) and strontium (< 0.947 mg/kg) have been found in milk at levels that do not constitute a health risk; furthermore their presence could be related to the geographical origin. An important presence of strontium and copper was revealed in forages and drinking water. Strontium is naturally present in forage and soil of the Campania region. The presence of copper can be attributed to its extensive use in agronomic practices. The presence of chemical elements in milk could be a tool for geo-referenced traceability down to small-scale, regional soil background levels.